If $x^2+y^2=t+\frac{1}{t}$ and $x^4+y^4=t^2+\frac{1}{t^2}$, then $\frac{d y}{d x}$ is equal to |
$\frac{y}{x}$ $-\frac{y}{x}$ $\frac{x}{y}$ $-\frac{x}{y}$ |
$-\frac{y}{x}$ |
We have, $x^2+y^2=t+\frac{1}{t}$ and $x^4+y^4=t^2+\frac{1}{t^2}$ $\Rightarrow \left(x^2+y^2\right)^2=\left(t+\frac{1}{t}\right)^2$ $\Rightarrow x^4+y^4+2 x^2 y^2=t^2+\frac{1}{t^2}+2$ $\Rightarrow x^4+y^4+2 x^2 y^2=x^4+y^4+2$ $\Rightarrow x^2 y^2=1 \Rightarrow 2 x y^2+2 x^2 y \frac{d y}{d x}=0 \Rightarrow \frac{d y}{d x}=-\frac{y}{x}$ |